1974
DOI: 10.1037/h0036419
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the rat's startle reaction by an antecedent change in the acoustic environment.

Abstract: A series of experiments related inhibition and facilitation of the startle response, elicited by an intense auditory signal, to a change of the frequency characteristic of a 70-db. continuous acoustic signal. The data indicated that if a frequency change occurs in the acoustic environment 64 msec, before the startle-eliciting stimulus, the amplitude of the startle response is reduced; and if frequency change occurs 4 msec, prior to the startle-eliciting stimulus, the response latency is reduced. These results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
35
2

Year Published

1984
1984
2001
2001

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 18 publications
11
35
2
Order By: Relevance
“…The amount of inhibition produced by the offset condition was equal to that produced by the gap-no shift condition and less than that produced by the shiftgap and onset conditions. The finding that the onset condition produced more inhibition than did the offset condition is contrary to previous reports of equivalent amounts of inhibition (Hoffman & Stitt, 1980;Stitt, Hoffman, & Marsh, 1973;Stitt et at, 1974). The differences may lie in the nature of the stimuli employed; for instance, the previous studies used bands of noise, whereas the present study employed pure tones.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The amount of inhibition produced by the offset condition was equal to that produced by the gap-no shift condition and less than that produced by the shiftgap and onset conditions. The finding that the onset condition produced more inhibition than did the offset condition is contrary to previous reports of equivalent amounts of inhibition (Hoffman & Stitt, 1980;Stitt, Hoffman, & Marsh, 1973;Stitt et at, 1974). The differences may lie in the nature of the stimuli employed; for instance, the previous studies used bands of noise, whereas the present study employed pure tones.…”
Section: Discussioncontrasting
confidence: 55%
“…Each subject received 12 blocks of trials, each block containing a different randomization of the four stimulus condiThe next step in this series of studies was to determine whether a shift in tonal frequency across a gap in acoustic stimulation would lead to any further reflex inhibition than a gap condition with no frequency shift. Previous work (Marsh, Hoffman, Stitt, & Schwartz, 1975;Stitt et al, 1974) had already indicated that shifts between high-and low-frequency bands of noise could inhibit a startle reflex; the question addressed here was whether similar effects could be obtained when the basic acoustic signal was a tone rather than noise, and when the frequency shift occurred across a gap in a signal that had a slow enough rise time (20 msec) that it would be transient free.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous work (Marsh, Hoffman, Stitt, & Schwartz, 1975;Stitt et al, 1974) indicated that shifts between high-and lowfrequency bands of noise could inhibit a startle reflex. The question addressed in this experiment was whether similar effects could be obtained when the basic acoustic prestimulus was a pure tone rather than narrowband.…”
Section: Methodsmentioning
confidence: 99%
“…Investigation of the reflex modification afforded by complex acoustic events began with the work of Stitt, Hoffman, Marsh, and Boskoff (1974). They found that if a small change in the intensity or the frequency of This research was supported by Grant HD 10511 to Howard S. Hoffman from the National Institutes of Health.…”
mentioning
confidence: 99%